2014
DOI: 10.1515/tjeb-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

Time Series Analysis About The Relationship Between Foreign Trade and Exchange Rate in Turkish Economy

Abstract: In this study, the relationship between the foreign trade data and the exchange rate is tested using the monthly data for the period of 1992:01-2014:01 in Turkish Economy. The devaluation of local currency is expected to increase export while decreasing import rates, thus it will close the foreign trade deficit, theoretically. However, this effect is observed in varying degrees in the on both short and long terms. One of the most fundamental problems of the Turkish Economy is the foreign trade deficit, beside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Vural () claimed that real exchange rate and trade balance are not correlated in Turkey. Against this submission, Kargi () verified that in the long run, exchange rate is related to export, import and net foreign trade in Turkey, which is also confirmed by Asteriou et al . () in Mexico, Indonesia and Turkey (MINT countries).…”
Section: Literature Reviewsupporting
confidence: 57%
“…Vural () claimed that real exchange rate and trade balance are not correlated in Turkey. Against this submission, Kargi () verified that in the long run, exchange rate is related to export, import and net foreign trade in Turkey, which is also confirmed by Asteriou et al . () in Mexico, Indonesia and Turkey (MINT countries).…”
Section: Literature Reviewsupporting
confidence: 57%
“…After the 2008 global financial crisis, although the relationship between oil prices and the exchange rate was negative, it was concluded that the strength of the relationship increased. Kargı (2014) tested the existence of the relationship between oil prices, inflation, and GDP variables for Türkiye between 1988 and 2013 by using Engle-Grangar and Johansen cointegration analyses and Granger causality analysis. According to the results of the study, a cointegration relationship was determined between the variables in the period under consideration.…”
Section: Literaturementioning
confidence: 99%